1986
DOI: 10.1037/0022-3514.50.4.737
|View full text |Cite
|
Sign up to set email alerts
|

Communication of individual emotions by spontaneous facial expressions.

Abstract: We examine whether spontaneous facial expressions provide observers with sufficient information to distinguish accurately which of seven affective states (six emotional and one neutral) is being experienced by another person. Senders' facial expressions were covertly videotaped as they watched emotionally loaded slides. After each slide, senders nominated the emotion term that best described their affective reaction, and also rated the pleasantness and strength of that reaction. Similar nominations of emotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
107
2
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(119 citation statements)
references
References 26 publications
(46 reference statements)
8
107
2
2
Order By: Relevance
“…Other studies suggest that these sex differences depend on the type of emotion. Women are said to be better in recognizing facial expressions of fear and sadness (Mandal & Palchoudhury, 1985;Nowicki & Hartigan, 1988), while men are superior at identifying anger (Mandal & Palchoudhury, 1985;Rotter & Rotter, 1988;Wagner, 1986).…”
Section: Recognizing Emotionsmentioning
confidence: 99%
“…Other studies suggest that these sex differences depend on the type of emotion. Women are said to be better in recognizing facial expressions of fear and sadness (Mandal & Palchoudhury, 1985;Nowicki & Hartigan, 1988), while men are superior at identifying anger (Mandal & Palchoudhury, 1985;Rotter & Rotter, 1988;Wagner, 1986).…”
Section: Recognizing Emotionsmentioning
confidence: 99%
“…Studies investigating specific emotions have found that women are more expressive of sadness (e.g., Allen & Haccoun, 1976;Balswick & Avertt, 1977;Fujita et al, 1980;Rotter & Rotter, 1988;Schwartz et al, 1980;Zuckerman et al, 1975; but see Tucker & Riggio, 1988), disgust (e.g., Fujita et al, 1980;Rotter & Rotter, 1988;Tucker & Riggio, 1988;Wagner et al, 1993;Wagner etal., 1986;Zuckerman etal., 1975),fear(e.g.,Allen& Haccoun, 1976Rotter & Rotter, 1988;Schwartz et al, 1980;Wagner et al, 1993;Zuckerman et al, 1975), surprise (e.g., Fujita et al, 1980;Wagner et al, 1993;Wagner et al, 1986;Zuckerman et al, 1975), happiness or smiling (e.g., Balswick & Avertt, 1977;Barr & Kleck, 1995;Frances, 1979;Fujita et al, 1980;Halberstadt et al, 1988;Tucker & Riggio, 1988;Zuckerman et al, 1975; but see Wagner et al, 1986), and anger (e.g., Allen & Haccoun, 1976;Schwartz et al, 1980;Wagner et al, 1993;Zuckerman et al, 1975; but see Rotter & Rotter, 1988).…”
mentioning
confidence: 99%
“…That is, a number of studies have found women to be more expressive than men using a variety of expression measures, such as EMG (e.g., Greenwald, Cook, & Lang, 1989;Lang, Greenwald, Bradley, & Hamm, 1993;Schwartz, Brown, & Ahem, 1980), ratings of communication accuracy (e.g., Buck, Baron, Goodman, & Shapiro, 1980;Buck, Miller, & Caul, 1974;Buck, Savin, Miller, & Caul, 1972;Fujita, Harper, & Wiens, 1980;Rotter & Rotter, 1988;Wagner, Buck, & Winterbotham, 1993;Wagner, MacDonald, & Manstead, 1986;Zuckerman, Lipets, Hall Koivumaki, & Rosenthal, 1975), self-report of expression (e.g., Allen & Haccoun, 1976;Balswick & Avertt, 1977;Gross & John, 1995;Kring et al, 1994), and ratings of a variety of nonverbal behaviors such as smiling and gesturing (e.g., Barr & Kleck, 1995;Frances, 1979;Halberstadt, Hayes, & Pike, 1988;Notarious & Johnson, 1982;Ragan, 1982;Riggio & Friedman, 1986). Although fairly rare, some studies have failed to find sex differences in expressiveness (e.g., Cupchik & Poulos, 1984;Fridlund, 1990;Lanzetta, Cartwright-Smith, & Kleck, 1976;Vrana, 1993;Wagner, 1990;Zuckerman, Hall, DeFrank, & Rosenthal, 1976).…”
mentioning
confidence: 99%
“…Researchers have used a range of methods to compare dynamic and static images that has included dynamically morphing a sequence of still images (Kamachi et al, 2001), animating synthetic images (Wehrle, Kaiser, Schmidt, & Scherer, 2000), and presenting film of spontaneous responses to emotional slides (Wagner, MacDonald, & Manstead, 1986). All of these studies have employed a recognition paradigm in which observers are asked, after viewing the stimulus, to judge what emotion was being displayed.…”
mentioning
confidence: 99%